Transparency in Government Operations - Kopits, George (Occasional Papers; Occasional Paper ;, 1998)
Transparency in government operations is widely regarded as an important precondition for macroeconomic fiscal sustainability, good governance, and overall fiscal rectitude. Notably, the Interim Committee, at its April and September 1996 meetings, stressed the need for greater fiscal transparency. Prompted by these concerns, this paper represents a first attempt to address many of the aspects of transparency in government operations. It provides an overview of major issues in fiscal transparency and examines the IMF's role in promoting transparency in government operations.